Improving Student’s Critical Thinking Skills in Mathematics Education: A Systematic Literature Review - Sari, Riska Novia; Juandi, Dadang (Mathematics Education Study Program, 2023)
Improving students' critical thinking skills is the goal of 21st-century learning. Therefore, this Systematic Literature Review (SLR) aims to find the techniques for improving students' critical thinking skills, especially in mathematics education. Data collection was obtained from scopus database. 24 publications published between the years 2018 to 2022 were retrieved for further analysis. Various tools were employed, they are; Microsoft excel and VostViewer. The result of the analysis showed that the techniques used to improve critical thinking skills include teaching methods, teaching materials, robotic coding activities, teacher attitudes, and the Olympics. The teaching method mostly used to improve critical thinking in mathematics education which is popularly used is Problem Based Learning (PBL) and Science Technology Engineering Mathematics (STEM) approach. This literature review is intended to help educators better understand learning tools to enhance students' critical thinking skills. This can make the mathematics learning process more creative and meaningful.